Spy x family. 6 - Endō, Tatsuya, 1980- (Shonen Jump manga., 2021)
Master spy Twilight is unparalleled when it comes to going undercover on dangerous missions for the betterment of the world. But when he receives the ultimate assignment - to get married and have a kid - he may finally be in over his head! Twilight and Nightfall enter an underground tennis tournament, hoping for an opportunity to obtain an intelligence document that threatens to bring the world to the brink of war! But will their mission be compromised by Nightfall's secret crush on Twilight?!